2019
DOI: 10.1039/c9an01078e
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of bisulfate in edible plant foods, dog urine, and drugs: picomolar level detection and bio-imaging in living organisms

Abstract: Picomolar level nonchemodosimetric probing of bisulfate in pure aqueous buffer at neutral pH by mechanosynthesized zwitterions and their unprecedented application in the estimation of bisulfate in edible plant foods, drugs, and urine samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…This probe can be applied to detect HSO3 − /SO3 Figure 62) can be used to develop a cheap, easy-to-prepare and easy-to-use paper test strip system for the detection of (bi)sulfites. A more recent example is a probe developed by Nair and collaborators, able to selectively detect the amphiphilic bisulfate ion (HSO4 − ) in edible plant foods, dog urine and drugs [256]. Bisulfate consumption normally takes place through the ingestion of different edible plants, such as cabbage, broccoli, Brussels sprouts, horseradish or seeds (black and white mustard, for instance).…”
Section: Food Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…This probe can be applied to detect HSO3 − /SO3 Figure 62) can be used to develop a cheap, easy-to-prepare and easy-to-use paper test strip system for the detection of (bi)sulfites. A more recent example is a probe developed by Nair and collaborators, able to selectively detect the amphiphilic bisulfate ion (HSO4 − ) in edible plant foods, dog urine and drugs [256]. Bisulfate consumption normally takes place through the ingestion of different edible plants, such as cabbage, broccoli, Brussels sprouts, horseradish or seeds (black and white mustard, for instance).…”
Section: Food Systemsmentioning
confidence: 99%
“…In addition, bisulfate salts of many APIs are currently on market, constituting another source of bisulfate ions [260]. When trying to evaluate the actual concentration of HSO4 − , it is important to take account of the deprotonation equilibrium between HSO4 − and SO4 2-, A more recent example is a probe developed by Nair and collaborators, able to selectively detect the amphiphilic bisulfate ion (HSO 4 − ) in edible plant foods, dog urine and drugs [256]. Bisulfate consumption normally takes place through the ingestion of different edible plants, such as cabbage, broccoli, Brussels sprouts, horseradish or seeds (black and white mustard, for instance).…”
Section: Food Systemsmentioning
confidence: 99%
“…Nair et al reported mechanochemical Betti reaction for the synthesis of two coumarin-based zwitterionic dyes ( 48a , b ) and the applicability in the detection of bisulfate ions at the picomolar level . The dyes were synthesized by grinding 7-hydroxy-4-methylcoumarin ( 47 ), formaldehyde, and glycine or alanine in a mortar and pestle in the presence of a small amount of methanol for 15 min to afford the products in good yields (63–64%).…”
Section: Mechanochemical Synthesis and Modification Of Fluorophores F...mentioning
confidence: 99%
“…48a,b) and the applicability in the detection of bisulfate ions at the picomolar level. 47 The dyes were synthesized by grinding 7-hydroxy-4-methylcoumarin (47), formaldehyde, and glycine or alanine in a mortar and pestle in the presence of a small amount of methanol for 15 min to afford the products in good yields (63−64%). The dyes recognize bisulfate ions by a color change from blue to colorless, and a turn-off response at emission maxima 448 nm was observed due to the formation of H-bonds between 48 and HSO 4 − (Figure 4B).…”
Section: Mechanochemical Synthesis and Modification Of Fluorophores F...mentioning
confidence: 99%
“…12 In fact, the World Health Organization (WHO) has stated that iodine deficiency is one of the biggest cause for intellectual disability on a global scale. 13 Hydrogen sulfate (HSO 4 − ) ions dissociate to produce noxious sulfate (SO 4 2− ) at high pH, 14,15 triggering skin irritation, eyes, and even respiratory paralysis. 16 Therefore, developing reliable methods for the quantification of the above trace ions in the environmental samples is of great significance for clarifying their toxic and other biological effects.…”
Section: Introductionmentioning
confidence: 99%